Analysis of the Calculation of Cost of Production in the Semoga Laris Tofu Business , the Chinese Tofu Business Mrs. Feby and the Sumedang Tofu Business - Rezky Oktasari Sesti; Nasib Subagio; Christie Stephanie Piar (Educational Studies: Conference Series, 2021)
This study aims to determine the differences in the calculation of the cost of production carried out by the Semoga Laris Tofu Business, Ibu Feby's Chinese Tofu Business and the Sumedang Tofu Business using the calculation of the cost of production method to produce one type of goods. This study uses quantitative descriptive analysis techniques while the data collection techniques used are interviews, observation and documentation. The data analysis technique used is the Calculation of Cost of Production Analysis to produce one type of goods. Based on the results of the general analysis, the calculation results of the cost of production at the Tofu Business are selling out Rp. 8,587, the calculation of the cost of production at the Chinese Tofu Business, Mrs. Feby, is Rp. 18,149 and the calculation of the cost of production at the Sumedang Tofu Business is Rp. 10,950, where the selling price of the Tofu Business is Good. The selling price is Rp. 10,000/kg, the selling price of Ibu Feby's Chinese Tofu Business is Rp. 20,000/Kg and the selling price of Sumedang Tofu Business is Rp. 24,000/kg. The results showed that the calculation of the cost of production produced one type of goods when compared to the cost of goods manufactured used by the Semoga Laris Tofu Business, Ibu Feby's Chinese Tofu Business and the Sumedang Tofu Business gave different results, which was greater using the cost of production method producing one types of goods. This is because the calculations carried out by the Semoga Laris Tofu Business, the Chinese Tofu Business Mrs. Feby and the Sumedang Tofu Business have not been right in charging factory overhead costs.